2021
DOI: 10.1186/s12939-021-01552-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the ageing workforce: global perspectives on needs and solutions across 15 countries

Abstract: Background COVID-19 has a direct impact on the employment of older people. This adds to the challenge of ageism. The World Health Organization has started a worldwide campaign to combat ageism and has called for more research and evidence-based strategies that have the potential to be scaled up. This study specifically aims to identify solutions to combat the adverse effects of COVID-19 on the global ageing workforce. Methods We present 15 case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…The third research question asked how country characteristics shape the situation of older workers in digitalizing workplaces. Previous research showed that the country-wide use of ICT, governmental programs for older workers' computer training, labor market structures, culture, THE JOURNAL OF AGING AND SOCIAL CHANGE welfare policies, and governmental responses to the COVID-19 pandemic are influential Grigoli, Koczan, and Topalova 2022;Pit et al 2021;. Interestingly, some of these influences are intended to shape the situation of older workers in digitalizing workplaces, such as the computer training programs and retirement regulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third research question asked how country characteristics shape the situation of older workers in digitalizing workplaces. Previous research showed that the country-wide use of ICT, governmental programs for older workers' computer training, labor market structures, culture, THE JOURNAL OF AGING AND SOCIAL CHANGE welfare policies, and governmental responses to the COVID-19 pandemic are influential Grigoli, Koczan, and Topalova 2022;Pit et al 2021;. Interestingly, some of these influences are intended to shape the situation of older workers in digitalizing workplaces, such as the computer training programs and retirement regulations.…”
Section: Discussionmentioning
confidence: 99%
“…The same governments, as well as the Austrian, Israeli, South Korean, and the US, supported education and training. Thus, they tried to enhance the skill levels of older workers, making it easier for them to navigate digitalization at work (Pit et al 2021). These country differences in the governmental reaction to the COVID-19 pandemic will translate into new country differences in how older workers fare in digitalizing workplaces.…”
Section: Governmental Policies For the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, new organizational business models, such as platform work (eg, Uber), and evolving worker preferences, such as remote work [6], have led to technological changes in the workplace. COVID-19 has also demonstrated the "forced innovation" such as the implementation of telehealth [7], increased use of videoconferencing, and technological solutions created during COVID-19 to support an aging workforce [8].…”
Section: Aging Workforce and Technological Changesmentioning
confidence: 99%
“…Given the rise of nonstandardized employment globally, such as gig work and short-term contracts, governments play a crucial role in ensuring the OHS of workers, through developing new concepts of decent work, organizing of networks among independent workers, and standardization of OHS regulations [32]. A recent study [8] reported case studies from 15 countries to address the impact of COVID-19 on aging workers and included many technological solutions such as next-generation age-inclusive manufacturing systems in Germany or an AI system run by a large Korean telecommunications company (SK Telecom) that continuously tracks the health of service users to reduce workload for health care staff.…”
Section: Principal Findingsmentioning
confidence: 99%